WEBINAR “SANTAP SEHAT ALA RUMAHAN DI ERA PANDEMI COVID-19” DI RT 02 KELURAHAN PULO GEBANG KECAMATAN CAKUNG PROVINSI DKI JAKARTA - Marshel Valentino; Luthfia Vionita; Siwi Rizki Utami; Shafira Nurul Ramadhani; Shara Nuzila Ramadhani; Rifdah Dinda Qatrunnada (Jurnal Layanan Masyarakat (Journal of Public Services), 2020)
Covid-19 is an infectious disease that is closely related to a person's nutritional status, for the fulfillment of nutrition- a mother in a family has a very important role in fulfilling the nutrition of family members (Ministry of Health of the Republic of Indonesia, 2020). The purpose of this webinar activity is to increase the knowledge of a mother in family welfare program in RW 02 Pulo gebang - Cakung, East Jakarta regarding the importance of fulfilling the nutrition of family members who will be directly related to individual health. A total of 17 respondents participated in the webinar using a qualitative analysis approach using 3 stages of activities, (1) measuring initial knowledge with pre-test, (2) treatment by learning material in the form of a webinar, ending the re-measurement of knowledge after the delivery of material in the form of post- test. The results of the presentation of the material were said to be successful because the final results showed that there were 76.5% of participants having increased knowledge.abstrakCovid-19 merupakan penyakit infeksi yang erat kaitannya dengan status gizi seseorang, untuk pemenuhan gizi dalam keluarga- seorang ibu memiliki peran yang sangat penting dalam pemenuhan gizi anggota keluarga (Kementerian Kesehatan RI, 2020). Tujuan kegiatan webinar ini adalah untuk meningkatan pengetahuan ibu-ibu PKK di RW 02 Kelurahan Pulo gebang, Kecamatan Cakung, Jakarta Timur mengenai pentingnya pemenuhan gizi anggota keluarga yang akan langsung berhubungan dengan kesehatan individu. Sejumlah 17 ibu PKK mengikuti webinar menggunakan metode pendekatan secara analisis kualitatif menggunakan 3 tahapan kegiatan yaitu (1) mengukur pengetahuan awal dengan pre-test, (2) treatment berupa pembelajaran materi dalam bentuk webinar, diakhiri pengukuran kembali pengetahuan setelah penyampaian materi dalam bentuk post-test. Hasil pemberian materi dikatakan berhasil karena hasil akhir menunjukkan bahwa terdapat 76,5% peserta memiliki peningkatan pengetahuan.